Technical Feasibility and Application of Mechanical Thrombectomy with the Solitaire FR Revascularization Device in Acute Basilar Artery Occlusion - Mordasini, P. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Acute BAO is a devastating neurological condition associated with a poor clinical outcome and a high mortality rate. Recanalization has been identified as a major prognostic factor for good outcome in BAO. Mechanical thrombectomy using retrievable stents is an emerging treatment option for acute stroke. First clinical trials using stent retrievers have shown promising high recanalization rates. However, these studies mainly included large artery occlusions in the anterior circulation with only a few or single cases of BAO. Therefore, the purpose of this study was to evaluate technical feasibility, safety, and efficacy of mechanical thrombectomy using retrievable stent in the treatment of acute BAO. MATERIALS AND METHODS: Fourteen consecutive patients with BAO undergoing endovascular therapy using retrievable stents (Solitaire FR Revascularization Device) were included. Additional multimodal treatment approaches included thromboaspiration, intravenous and/or intra-arterial thrombolysis, and PTA/ permanent stent placement. Recanalization rates after multimodal therapy and stent retrieval were determined. Clinical outcome and mortality were assessed 3 months after treatment. RESULTS: Median patient age was 64.5 years (range 55–85). Median NIHSS score at presentation was 21 (range 5–36). Overall, successful recanalization (TICI 3 or 2b) was achieved in all patients (TICI 3 in 78.6%, 11/14). In 4 patients (28.6%), insufficient recanalization after stent retrieval was due to an underlying atherosclerotic stenosis. Additional deployment of a permanent intracranial stent was performed in 3 patients (21.4%) and PTA alone in 1 patient (7.1%), resulting in final TICI 3 in 1 patient and TICI 2b in 3 patients. Stent retrieval alone was performed in 4 patients (28.6%). Average number of device passes was 1.3 (range 1–3). Median procedure time to maximal recanalization was 47 minutes (range 10–252). No device-related complications or thromboembolic occlusion of a previously unaffected artery occurred. There was no symptomatic intracranial hemorrhage. At 3 months, good functional outcome (mRS 0–2) was observed in 28.6% (4/14); overall mortality was 35.7% (5/14). CONCLUSIONS: A multimodal endovascular approach using retrievable stents in BAO has high recanalization rates, with very low complication rates. Underlying atherothrombotic stenotic lesions of the basilar artery may still necessitate additional permanent stent placement to achieve complete recanalization.